Comparative Study on Commercial Broiler Rearing Pattern in Plain and Coastal Regions of Bangladesh - Islam, MS; Hossain, MM; Kamal, MM; Hashem, MA (Journal of Environmental Science and Natural Resources, 2015)
The study was conducted at Sharsa, Jhikargacha, Chawgacha and Jessore sadar upazila of Jessore District regarded as plain and Lalmohon, Borhanuddin, Daulatkhan and Bhola sadar upazila of Bhola District regarded as coastal region with a view to compare the present status and rearing pattern of broiler. Data were collected randomly from selected 52 broiler farmers through personal interview using an interview schedule. The highest number of broiler farmers 69.2% and 57.7% in Jessore and Bhola District, respectively belonged to middle aged group (31-50 years) involved in broiler farming. About 48.1% and 59.6% broiler fermers respondents of Jessore and Bhola District, respectively possessed secondary level of education involved in broiler farming. About 48.08% and 63.46% broiler farmers in Jessore and Bhola District, respectively disinfected their farm using lime water. About 40.38% broiler fermers administered vaccine against ranikhet, gumboro, infectious bronchitis diseases and 36.64% administered vaccine against ranikhet and gumboro diseases in Jessore and Bhola District, respectively. About 36.54% broiler fermers applied antibiotic against coccidiosis, dermatitis and respiratory infection diseases and 44.23% broiler fermers applied antibiotic against coccidiosis, dermatitis and respiratory infection diseases in Jessore and Bhola District, respectively. The highest number of broiler farmers in Jessore District faced great marketing problems due to unfavorable market for selling broiler, high price of feed and chick and in Bhola District the farmers faced great marketing problem due to the unstable and high price of feed and chicks. DOI: http://dx.doi.org/10.3329/jesnr.v6i1.22046 J. Environ. Sci. & Natural Resources, 6(1): 89-97 2013